Implementacion de indicadores kpi en los controles de los equipos “empernadores hammer bolt” para mejorar el rendimiento de los equipos en el sostenimiento mecanizado – mina catalina huanca sociedad minera s.a. - Rodríguez Custodio, Julio Cesar (2017)
The present thesis aims to analyze the performance of Hammer Bolt empernadores teams, which have been carrying out a stage of mining cycle that is the support, the support has been carried out in the work as forward fronts and production slits in The Mining Unit Catalina Huanca - Ayacucho. The performance of the equipment before and after the implementation of KPI indicators will be analyzed, to evaluate the performance in the installation of materials for the mechanized support since the decrease of this, causes delay in the mining cycle. These problems in the mining cycle was the motive that prompted me to carry out an implementation of KPI indicators in the operational controls of these equipments in order to increase the performance in the installation of support materials. For this the indicators that were handled are the availability, utilization, reliability and Maintainability of Hammer Bolt equipment. Achieving an increase of 8% in the performance of Hammer Bolt equipment in the installation of Split set, helical bolt and welded mesh. The research was based on the control of 3 Hammer bolt empernadores teams for 8 months before the implementation of the KPI indicators and during 4 months during the implementation of these indicators, which provided me with the necessary information to obtain the optimal KPI for these equipments , Thus improving the performance of the equipment in the installation of support materials, in the underground mining work of the Catalina Huanca Mining Unit.